P118 Abrams-Needle Pleural Biopsy Remains a Useful Investigation in Suspected Pleural Tuberculosis. (19th November 2012) - Brown, JP; Ricketts, WM; Bothamley, GH
Abstract : Current British Thoracic Society guidelines suggest that Abrams needle biopsy is only useful in areas of high incidence of tuberculosis and suggest that thoracoscopic pleural biopsy or image guided cutting-needle biopsies may be preferable.[1] A recent study suggested that the low yield of culture of pleural fluid may have improved with advancing culture techniques, perhaps reducing any advantage of pleural biopsy.[2] We therefore sought to establish whether or not Abrams-needle pleural biopsies contribute to the diagnosis of pleural tuberculosis in an urban UK setting with an annual incidence of tuberculosis between 60 and 125/100, 000. Methods: We reviewed all cases treated for pleural tuberculosis in two inner-city hospitals between 2006 and 2011. The yield of culture of pleural fluid was determined, and for those who underwent a pleural biopsy the yield from culture or typical histological changes was determined. Results: We identified 150 patients with pleural tuberculosis since 2006. In our series, a positive culture from pleural fluid was achieved in 45 of 148 where pleural fluid was send without biopsy at the same procedure (30%; upper 95% confidence interval 39% using Wilson's procedure with continuity correction). 44 patients underwent a pleural biopsy, of which 28 had positive histology or culture (63%; 95% confidence interval 48%-76%). The difference in sensitivity of these tests was statistically significant (p = 0.0002). Conclusion: The management of a unilateral pleural effusion where tuberculosis is a likely diagnosis poses a clinical dilemma. Empirical treatment for tuberculosis risks the mismanagement of drug-resistant disease or missing alternative diagnoses, and yet thorascopic pleural biopsy is an invasive procedure with significant potential complications. Our data suggest that the yield from culture of pleural fluid alone remains poor and there remains a place for the Abrams-needle biopsy in these circumstances. Investigation of a unilateral pleural effusion in adults – British Thoracic Society Pleural Disease Guideline 2010 Clare Hooper, YC Gary Lee, Nick Maskell Thorax, Vol 65, Suppl 2. Ruan SY et al. Revisiting tuberculous pleurisy: pleural fluid characteristics and diagnostic yield of mycobacterial culture in an endemic area. Thorax . 2012 Mar 21